2012
DOI: 10.7314/apjcp.2012.13.4.1407
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Findings in a Mass Screening Program for Gastric Cancer in a High Risk Region - Guilan Province of Iran

Abstract: Background & Objectives: Gastric cancer is a leading cause of cancer-related deaths in both sexes in Iran. This study was designed to assess upper GI endoscopic findings among people > 50 years targeted in a mass screening program in a hot-point region. Methods: Based on the pilot results in Guilan Cancer Registry study (GCRS), one of the high point regions for GC -Lashtenesha-was selected. The target population was called mainly using two methods: in rural regions, by house-house direct referral and in urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In Iran, this is a very important fact as this country is categorized as an intermediate-risk area, where the seroprevalance of H. pylori infection reaches 62-90% (Malekzadeh et al, 2004;Islami and Kamangar, 2008;Mansour-Ghanaei et al, 2012a, 2012b. Some parts of Iran are also considered high-prevalence areas (Hossein Somi et al, 2006;Malekzadeh et al, 2009;Mansour-Ghanaei et al, 2012a, 2012b. In the present study, the prevalence of precancerous lesions including atrophy, IM, and dysplasia and their relation with some common risk factors were evaluated in a population of chronic dyspeptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, this is a very important fact as this country is categorized as an intermediate-risk area, where the seroprevalance of H. pylori infection reaches 62-90% (Malekzadeh et al, 2004;Islami and Kamangar, 2008;Mansour-Ghanaei et al, 2012a, 2012b. Some parts of Iran are also considered high-prevalence areas (Hossein Somi et al, 2006;Malekzadeh et al, 2009;Mansour-Ghanaei et al, 2012a, 2012b. In the present study, the prevalence of precancerous lesions including atrophy, IM, and dysplasia and their relation with some common risk factors were evaluated in a population of chronic dyspeptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lashtenesha has a population over 45000 persons (49.6% males, 50.4% females), among them 10500 persons have >50 years old. Most of the people settled in rural regions (70.0%) (Mansour-Ghanaei et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Prevention unpublished works regarding cancerrelated death in Guilan province during 1999-2002 in the Gastrointestinal and Liver Diseases Research Center (GLDRC) confirmed gastric cancer as the leading cause of cancer-related death which led to 31.4% of all cancer deaths over the province; These emerged the necessary of surveillance programs for GC especially among high risk population (Mansour-Ghanaei et al, 2010). This study is a part of a large-scaled study in hot point regions for GC designed to assess prognostic value of screening biomarkers like pepsinogen I/II and Gastrin among people >50 years as a cost-effective screening method for early detection of gastric carcinoma.…”
mentioning
confidence: 99%
“…In Iran, performance of national-level endoscopy screening was effective for a high-risk region. (Mansour-Ghanaei et al, 2012) The costeffectiveness of mass screenings may also vary according to the cost of the screening examination. For example, endoscopic screening costs in Korea are less than 50% of those in other countries, like Japan and Singapore (Chang et al, 2012).…”
mentioning
confidence: 99%